NON PERFORMING FINANCIAL (NPF) MEMODERASI PEMBIAYAAN MUDHARABAH DAN MUSYARAKAH TERHADAP PROFITABILITAS - SURYADI, NANDA; YUSNELLY, ARIE; NURAINI, RATNA; GUSTINA, IRA (Fakultas Ekonomi Universitas Islam Indragiri, 2024)
The purpose of this study is to test the hypothesis and generate evidence regarding the effect of Mudharabah, Musyarakah contract financing on profitability with Non-Performing financing (NPF) as a moderating variable at Islamic People's Financing Banks (BPRS) in 2021-2023. This study uses secondary data, namely the BPRS financial statements published in the Financial Services Authority (OJK) which determine the effect of Mudharabah, Musyarakah and Murabahah contract financing on profitability with Non-Performing financing (NPF) as a moderating variable at the Islamic People's Financing Bank (BPRS) in 2021-2023. The sampling used in this study was purposive sampling method. The number of BPRS sampled in this study was 29 banks. The analysis method used to test the hypothesis is Eviews 12. The results of this study indicate that Mudharabah Financing has a negative and insignificant effect on Profitability, but Musyarakah Financing has a positive and significant effect on Profitability.